(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the interrelation and shared objectives of medicine, law, and fiqh (Islamic jurisprudence) in protecting human life and dignity. It examines the role of medicine in preserving human health, the function of the legal system in guaranteeing human rights, and the principles of Islamic law concerning the protection of human life and honor. On the basis of medical deontology, bioethics, national legislation, and juridical (fiqh) maxims, the article reveals the scientific and practical significance of these three domains.